Diagnóstico de la evasión tributaria del impuesto al valor agregado en el cantón Bolívar en el período 2012-2013 - Morrillo Zambrano, María Gema (2015)
The objective of this research was to diagnose the causes of evasion of VAT taxpayers assets in the canton Bolívar, for this purpose a multistage process was designed, the first allowed insight into issues related to taxation and respect VAT, the second was to identify and analyze the source of the problem, for this method (inductive - deductive, analysis, synthesis) were used technique (survey: 338 taxpayers - 367consumidores) and software (SPSS-DIMM), the same as allowed investigate, enter and retrieve data to arrive at the results, where the percentage of evasion (50%) was determined, the reliability of the survey was checked by the method of internal consistency based on Cronbach's alpha using the Software SSPS (0 lack of tax obligations, proof deficient emission process, insufficient control on the records of purchases-sales: 97% -0.90%) conducted surveys also major factors affecting VAT and are evidenced or services, lack of consumer awareness, poor understanding of the importance of the tax; in the third stage the proposal for an action plan designed to reduce by 50% the gap in tax evasion of VAT, ending with the last stage where a proposed action plan to the Regional Directorate socialized Internal Revenue Service Manabi for taking corrective action, thus the proposed action plan reconciles the different guidelines to guide the level of tax evasion to increase annual revenues in the country.